Utilisation of water-in-oil-water (W1/O/W2) double emulsion in a set-type yogurt model for the delivery of probiotic Lactobacillus paracasei. (May 2018) - El Kadri, Hani; Lalou, Sofia; Mantzouridou, FaniTh; Gkatzionis, Konstantinos
Abstract: W1 /O/W2 emulsion in set-type yogurt has the potential to segregate probiotics in order to avoid interference with the starter culture as well as protection against harsh processing and digestion conditions. Lactobacillus paracasei subsp. paracasei DC 412 probiotic cells in milk-based W1 /O/W2 emulsions were incorporated in yogurt, in addition to starter cultures Lactobacillus bulgaricus and Streptococcus thermophilus, and the effect on the fermentation, bacterial growth kinetics, physicochemical properties, and structural characteristics was investigated. Stability of W1 /O/W2 was monitored with optical microscopy and cryo-SEM and localisation of encapsulated L. paracasei in yogurt was monitored using fluorescent microscopy. During fermentation, starter culture was not affected by introduction of L. paracasei and/or W1 /O/W2 emulsion. The viability of L. paracasei encapsulated in W1 /O/W2 emulsion was enhanced during storage and after exposure to simulated gastrointestinal conditions. L. paracasei remained within the inner W1 phase till the end of the storage period (28 days at 4 °C). Moreover, W1 /O/W2 emulsion altered physicochemical and textural properties; however, these were within acceptable range. These results demonstrate the capability of W1 /O/W2 emulsion to be utilised for probiotic fortification of yogurt to increase functionality without interfering with starter culture and fermentation. Graphical abstract: Highlights: First study to utilise W1 /O/W2 emulsion for probiotic delivery in set-type yogurt. Lactobacillus paracasei viability increased during 28-day storage at 4 °C. L. paracasei remained encapsulated throughout storage. L. paracasei viability in gastric juice increased throughout storage. W1 /O/W2 emulsion affected set-type yogurt physicochemical and textural properties.